Clinicopathological and Gene Mutation Analysis of 27 Cases with Extranodal Rosai–Dorfman Disease [Corrigendum] - Tang M; Gu XZ; Wu PC; Yang XT (Journal of Inflammation Research, 2022)
Tang M, Gu XZ, Wu PC, Yang XT. J Inflamm Res. 2022;15:2775-2787. The authors have advised that there is an error in affiliation 2 on page 2775, “Yunnan Blood Disease Clinical Medical Research Center” should read “Yunnan Province Clinical Research Center for Hematologic Disease”. The authors apologize for this error. Read the original article